Valuation of subsoil minerals in Bangladesh: An application of the system of environmental-economic accounting. (August 2019) - Kabir, Mahfuz; Salim, Ruhul
Abstract: This study applies an alternative accounting framework that is the System of Environmental-Economic Accounting (SEEA) to undertake a valuation of the two most important sub-soil minerals, namely natural gas and coal, in Bangladesh. This framework outlines the method of preparing physical and monetary balance sheets of these two sub-soil minerals. Our empirical results show that the physical stock of natural gas has been diminishing rapidly because of its present excessive consumption in many sectors. The annual reduction of stock ranged from 6.94 to 7.56 per cent of the monetary value of the stock between 2011–12 and 2016–17 with fluctuations over time. However, the depletion rate of the stock of coal is much lower and ranges around 0.023 to 0.056 per cent of the monetary value of the stock. Furthermore, the value of the stock of both the minerals has been found to be highly sensitive to the choice of discount rate; for a lower discount rate the value of stock is higher, and vice versa. Highlights: The System of Environmental-Economic Accounting (SEEA) is applied to undertake a valuation of sub-soil minerals. This technique gives physical and monetary balance sheets of sub-soil minerals. The GDP coming from the subsoil minerals turns out to be higher than that of traditional SNA. The value of stock of minerals found to be highly sensitive to the choice of discount rate.